INTEGRAL APPROACH TO CULTURAL REFORM: AN INDONESIAN CRIMINAL JUSTICE SYSTEM - Abdurrakhman Alhakim (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
Legal reform requires an approach to various aspects of the law itself. It works the same way in criminal law, the reform does consider not only a collection of written norms but also other aspects such as structure and culture. Furthermore, an integral reform must cover three elements of the legal subsystem because if reforms in other subsystems do not accompany it, the reform will only be a dream. Thus, the reform can create legal effectiveness in providing certainty, benefit, and justice. Based on the urgency and description, this research is considered important to be carried out. This study aims to highlight the renewal of criminal law in legal culture and the various obstacles and concepts offered. Based on this background, several problems will be obtained to be discussed. This legal research uses doctrinal research methods with a conceptual and statutory approach. Various scientific approaches are needed in cultural renewal, including religious scientific, contextual, and comparative juridical approaches. With these three approaches, the cultural renewal will provide new aspects of criminal law and its usefulness, representing a sense of justice in society.